Persistence and Breaking Dormancy of Sintanur Variety Rice Seed - Aldi Kamal Wijaya; Yoni Andari; Setyono; Punjung Medaraji Suwarno; Ridwan Diaguna (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2025)
Research on breaking seed dormancy in rice is essential for understanding dormancy-breaking methods and their persistence, as dormancy behavior varies among rice varieties. This study aimed to examine the persistence of dormancy and effective dormancy-breaking methods in Oryza sativa L. cv. Sintanur. The research used two seed lots of the Sintanur variety—new and old lots—arranged in a split-plot design with two factors: dormancy-breaking treatments (control, 24-hour hydration, 48-hour hydration, KNO₃ solution, and GA₃) and storage periods (0, 1, 2, 3, and 4 weeks after harvest). The results showed that seeds of the Sintanur rice variety exhibited dormancy with persistence up to 3 weeks. The interaction between dormancy-breaking treatments and storage period significantly affected germination percentage, normal seedling growth, and seedling dry weight. Treatment with 10 ppm GA₃ for 48 hours effectively broke seed dormancy in the Sintanur variety starting from 1 week after harvest.